Comparative Proteomic Analysis Reveals Novel Biomarkers for Gastric Cancer in South Indian Tamil Population - Sivagnanam, Ananthi; Thangasamy, Balasankar; Nagarajan, Vignesh; Ravi, Subeksha G.; Madhesh, Jeevitha Chithra; Perumal, Manikandan Athilinga; Karunakaran, Premkumar; Jayaraman, Megala (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Gastric Cancer (GC) remains a major global health problem due to a poor understanding of its progression at the molecular level and a lack of early detection or diagnosis. Early detection is highly crucial for improving prognosis. The incidence of GC is very high in countries, like India, due to the limitations among the established biomarkers for GC owing to poor sensitivity and specificity. Objective: This study aimed to identify the novel biomarkers from serum samples obtained from GC patients compared to healthy subjects. Methods: Serum samples from GC patients were analyzed by two-Dimensional Gel Electrophoresis (2DGE) coupled with tandem Mass Spectrometry (MS), including both Matrix-Assisted Laser Desorption/Ionization-Time of Flight (MALDI-ToF) and Liquid Chromatography-MS (LC-MS/MS) analysis. Identified proteins were further analyzed by gene ontology and protein interaction studies. Results: A total of 73 protein spots were detected in 2DGE image analysis. Among them, seven differentially-expressed proteins were identified using MS analyses, including serotransferrin/ transferrin, albumin, ceruloplasmin, C-reactive protein (CRP), fibrinogen γ-chain (FGG), and two unreported novel proteins, immunoglobulin kappa constant (IgΚC) region and Homo sapiens zinc finger protein 28 (ZNF28) homolog. Among these proteins, serotransferrin, albumin, ceruloplasmin, FGG, and ZNF28 were down-regulated in GC samples (p<0.05), while IgΚC region and CRP were up-regulated significantly. Conclusion: Most of the differentially expressed proteins were involved in angiogenesis, plasminogen-activating cascade, and blood coagulation pathways which are known to play a critical role in gastric tumorigenesis. Our current results provide a panel of candidate biomarkers for GC with novel biomarkers which have not been reported earlier.
Keywords: LC-MS/MS analysis